Protective effect of vitamin C, vitamin B12 and omega-3 on lead-induced memory impairment in rat - Saeedeh Alsadat Moosavirad; Mohammad Rabbani; Mohammad Sharifzadeh; Ali Hosseini-Sharifabad (Wolters Kluwer Medknow Publications, 2016)
Lead belongs to the heavy metal group and is considered as an environmental contaminant. Acute or chronic contact to lead can change the physiological function of human organs. One of the most important disorders following the lead exposure is neurotoxicity. Lead neurotoxicity consists of the neurobehavioral disturbances like cognitive impairment. The aim of the current study is to evaluate the possible protective effect of vitamin C (Vit C), vitamin B12 (Vit B12), omega 3 (ω-3), or their combination on the lead-induced memory disorder. Adult wistar rats were orally administered Vit C (120 mg/kg/day) or Vit B12 (1 mg/kg/day) or ω-3 (1000 mg/kg/day) or their combination for 3 weeks in groups of 7 animals each. Then lead acetate (15 mg/kg/day) was injected intraperitoneally for one week to all pretreated animals. The control group received normal saline as a vehicle while the positive control for cognitive impairment received just lead acetate. At the end of treatments animal memories were evaluated in Object Recognition Task. The results showed, although 15 mg/kg lead acetate significantly declines the memory-evaluating parameters, pretreatment with Vit C, Vit B12, ω-3, or their combination considerably inverted the lead induced reduction in discrimination (d2) index (P < 0.001) and recognition (R) index (P < 0.001, P < 0.05, P < 0.05, and P < 0.001, respectively). Our findings indicate while lead acetate impairs spatial memory in rat, administration of Vit C, Vit B12, ω-3, or their combination prior to the lead exposure inhibits the lead induced cognitive loss. There was no remarkable difference in this effect between the used supplements.